A Far Cry from School History: Massive Online Open Courses as a Generative Source for Historical Research - Gallagher, Silvia; Wallace, Ciaran (International Review of Research in Open and Distributed Learning, 2016)
Current research into Massive Online Open Courses (MOOCs) has neglected the potential of using learner comments for discipline-specific analysis. This article explores how MOOCs, within the historical discipline, can be used to generate, investigate, and document personal narratives, and argues that they serve as a rich platform for historical resource generation. Through these narratives, this research explores changing perceptions of learning; from learning history at school to learning about history in a MOOC. This exploration uses a qualitative thematic analysis of learner comments related to personal narratives of learning history at school from the Trinity College Dublin/Futurelearn “Irish Lives in War and Revolution: 1912-1923” MOOC. These personal narratives were generated both directly and indirectly through four pedagogical tools; reflective questions, multimedia resources, external links, and inter-learner interaction. Broad themes emerged from the analysis of personal narratives including attitudes toward history at school, biased and inadequate teaching, and MOOC teaching compared with school experiences. The analysis demonstrated that MOOCs serve as a generative repository for personal and family historical narratives, and described how MOOCs can change perceptions of teaching and learning history. This paper contributes a novel understanding of MOOCs for discipline-specific analysis, provides a framework for MOOC historical resource generation, and describes changing perceptions of learning from the perspective of MOOC learners.